2018
DOI: 10.1002/tox.22565
|View full text |Cite
|
Sign up to set email alerts
|

GABA tea attenuates cardiac apoptosis in spontaneously hypertensive rats (SHR) by enhancing PI3K/Akt‐mediated survival pathway and suppressing Bax/Bak dependent apoptotic pathway

Abstract: Cardiomyocyte apoptosis is the major risk factor for the development of heart failure (HF). The purpose of this study was to evaluate the effects of Gamma-aminobutyric acid (GABA) tea on hypertension-induced cardiac apoptotic pathways in spontaneously hypertensive rats (SHR). In order to reveal the mechanisms, 36 male SHR at eight weeks of age, 200 g were divided into six groups. One group was fed water as a control group. Other rats were administered one of the following treatments: GABA tea at dose 150 and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Spontaneously hypertensive rats (SHR) 8-week-old (approx. 200 g), were acquired from the National Laboratory Animal Center (Taipei, Taiwan) and sustained following our previous protocol [10]. All animal experiments were performed in accordance with the Guide for the Care and Use of Laboratory Animals (National Institutes of Health Publication No.…”
Section: Methodsmentioning
confidence: 99%
“…Spontaneously hypertensive rats (SHR) 8-week-old (approx. 200 g), were acquired from the National Laboratory Animal Center (Taipei, Taiwan) and sustained following our previous protocol [10]. All animal experiments were performed in accordance with the Guide for the Care and Use of Laboratory Animals (National Institutes of Health Publication No.…”
Section: Methodsmentioning
confidence: 99%
“…Previous findings reported that PDCD5 and Tadalafil protect from the cardiac remodeling in mice model . Besides, the Tunel assay revealed that the SHR group showed higher apoptotic cells . To determine the molecular mechanism, we examined the protein markers for apoptosis, antiapoptosis, cell survival, autophagy, and mitochondrial biogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, SHR group showed upregulated caspase 3 and cytochrome c protein expression. Furthermore, the bioactive peptide‐treated SHR groups attenuated cardiac apoptosis through the enhancement of survival protein expressions (PI3K/Akt) …”
Section: Discussionmentioning
confidence: 99%
“…HIF-1 is the chief hypoxia-regulated transcription factor that can regulate cellular responses under hypoxic and ischemic conditions [55,56]. The PI3K/AKT pathway plays a seminal role in regulating multiple biological effects, including cell growth and proliferation, apoptosis, and angiogenesis [57]. The PI3K/AKT pathway The protein expression levels of IL-6, CCL2, and IL-1β in the left ventricle were evaluated by western blot analysis.…”
Section: Discussionmentioning
confidence: 99%